Complex palaeo-ice sheet dynamics in northeast Ireland during the retreat and reorganisation of the central British-Irish Ice Sheet - Alexander M. Clark; Bethan J. Davies; Sam Roberson; Simon P.E. Blockley; Adrian P. Palmer; Magret Damaschke (Geomorphology, 2026)

ACMT Position Statement: Preventing Cannabis Exposures in Children (2026) - Robert G. Hendrickson; Maryann Mazer-Amirshahi; Caitlin Bonney; Michele Burns; Diane P. Calello; Suzanne Doyon; Jeremy Hardin; Hannah Hays; Diane E. Hindman; Erica Liebelt; Michael J. Moss; Lewis Nelson; et al. (Journal of Medical Toxicology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Advancing stakeholder engagement in climate adaptation: a systematic review of structural barriers and operational enablers - Enora Bruley; Anna Scolobig; Marta Ellena; Sam Pickard; Mathilda Englund; Eulàlia Baulenas; Dmitry Erokhin; Sukaina Bharwani; Marina Mattera; Madeline Baldelli; Lucia Moreno; Judith Bielsa; et al. (Sustainability Science, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Food limitation erodes the thermal tolerance of larvae in an ecologically influential marine herbivore - Maya J. Munstermann; Sam E. Karelitz; Rachele Ferraro; Laura Rogers‐Bennett; Rachel D. Simons; Daniel K. Okamoto (Ecology, 2026)
Biologists often use organismal thermal tolerance to help explain or forecast responses of populations to climate change. Yet many studies quantify thermal tolerance under isolated laboratory conditions despite extreme events, such as heatwaves, often coinciding with other stressors such as nutrient or food limitation. These oversights may be consequential as recent theory suggests thermal tolerance itself can be fundamentally altered by food limitation. Here, we experimentally test how food limitation (500–10,000 cells mL −1 ) affects long‐term survival, development, and growth across a present‐day range of temperatures (10–20°C) in the most sensitive life stages of an important marine herbivore, purple sea urchins ( Strongylocentrotus purpuratus ). We show food limitation substantially erodes thermal tolerance in terms of survival, but when provided ample food, larvae exhibited robust survival across temperatures currently experienced by larvae in nature. Reductions in food however lowered optimal survival temperatures and shifted survival thresholds to those conditions observed during recent marine heatwaves. These results are consistent with the “metabolic meltdown” hypothesis—shifting optima and upper limits to cooler temperatures—and illustrate how present‐day warming coupled with lower productivity may lead to substantial, unexpected declines in larval survival and recruitment. In contrast to survival, developmental rates and time to metamorphic competency, which ranged from 21 to 61 days, were driven largely by temperature with little impact of food concentration. Our findings relate to historical observations of declines in larval supply at the southern edge of the species range. Overall, these results have broad‐reaching implications beyond sea urchin populations as sea urchin herbivory is known to control productivity of kelp forest communities. We provide evidence of how laboratory derived thermal reaction norms can be coupled with ecologically relevant food concentrations to inform unexpected vital rate declines of sensitive life stages in a changing climate.

Structuring the skies: Diel dynamics of migratory animal movement in the lower atmosphere - Silvia Giuntini; Carolyn S. Burt; Annika L. Abbott; Carrie Ann Adams; Maria Carolina T. D. Belotti; Yuting Deng; Miguel F. Jimenez; Jeffrey F. Kelly; Subhransu Maji; Meredith Nash‐Martin; Sam Simon; Daniel Sheldon; et al. (Ecology, 2025)
Earth's lower atmosphere is a vital ecological habitat, home to trillions of organisms that live, forage, and migrate through this medium. Despite its importance, this space is seldom considered a primary habitat for ecological or conservation prioritization, making it one of the least studied environments. However, it plays a crucial role as a global conduit for the transfer of biomass, weather, and inorganic materials. Fundamental research is essential to address core ecological questions related to the ecological consequences of this habitat's intricate spatial and temporal structure. To advance our understanding of airspace use by migratory animals, we analyzed over 108 million 5‐min radar observations from 143 NEXRAD sites, focusing on 24‐h diel cycles across the contiguous United States. This extensive dataset, spanning from 1995 to 2022, allowed us to quantify aerial space use by systematically identifying peak activity times, the portion of the airspace that contained the majority of migration activity, and the percentage of migrants passing across diurnal and nocturnal diel cycles. We found that airspace is used predominantly during nocturnal periods in both spring and autumn (88%), while summer exhibited a more balanced distribution (54% nocturnal). Additionally, the percentage of nocturnal activity increased with latitude in spring and autumn but decreased in summer. Peak aerial activity typically occurred about 4 h after local sunset in both spring and autumn, with variations based on latitude and longitude. During these peak times, on average, half of the aerial movement was confined within a vertical band of 516 meters, starting around 355 m above ground level. Our research underscores the need to view the lower atmosphere as a structured habitat with significant ecological importance.

A simple model to represent damage and fracturing in rock salt caused by heating and subsequent cooling: Understanding brine inflow data from the Brine Availability Test in Salt (BATS) - Claire Watson; Steven Benbow; Alexander Bond; Simon Norris; Sam Parsons (Geomechanics for Energy and the Environment, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The impact of uninterrupted sitting on central and peripheral cardiovascular function in pre-menopausal and post-menopausal women - Arsalan Moinuddin; Keeron Stone; Louise Turner; Craig Paterson; Nicky Hall; Anne Daykin; Sam Lucas; James Faulkner; Simon Fryer (European Journal of Applied Physiology, 2024)

Assessing the scale and ecological impact of derelict and discarded fishing gear across Thailand via the MARsCI citizen science protocol - Rahul Mehrotra; Coline Monchanin; Matthias Desmolles; Salisa Traipipitsiriwat; Dominic Chakrabongse; Amir Patel; Maythira Kasemsant; Sam Miyano Pitt; Tim McCabe; Trent McGrath; Claudia Marcellucci; Supatcha Japakang; et al. (Marine Pollution Bulletin, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Relationship Between Cognitive Functioning and Symptoms of Depression, Anxiety, and Post-Traumatic Stress Disorder in Adults with a Traumatic Brain Injury: a Meta-Analysis - Daniel Uiterwijk; Robyn Stargatt; Sam Humphrey; Simon F. Crowe (Neuropsychology Review, 2022)

Ficus trees with upregulated or downregulated defence did not impact predation on their neighbours in a tropical rainforest - Elina Mäntylä; Leonardo Ré Jorge; Bonny Koane; Katerina Sam; Simon T. Segar; Martin Volf; Alexander Weinhold; Vojtech Novotny (Arthropod-Plant Interactions, 2022)

Can Stomach Content and Microbiomes of Tuna Provide Near Real-Time Detection of Ecosystem Composition in the Pacific Ocean? - Alejandro Trujillo-González; Teng Li; Joanne Potts; Simon Nicol; Valerie Allain; Sam C. Godwin; Elodie Vourey; Annie Portal; Brian Kumasi; Thomas Usu; Allen Rodrigo; Dianne Gleeson (Frontiers in Marine Science, 2022)
This preliminary study used DNA metabarcoding to test whether the stomach content and gut microbiome of tuna could be a viable near real-time monitoring tool for detecting composition and change in oceanic ecosystems. The gut content of skipjack ( Katsuwonus pelamis , n=55) and yellowfin tuna ( Thunnus albacares , n=46) captured in the Pacific Ocean during El Niño Southern Oscillation events (ENSO) between 2015-2017 were examined by high throughput sequencing and complemented by morphological assessments to identify fishes, crustaceans and cephalopods in the stomach content. Gut microbiome was examined solely by high throughput sequencing. Stomach content and gut microbiome were compared between tuna species, ENSO events and capture location using generalised linear models. The full model (tuna species, capture location and interaction with ENSO) best explained fish prey composition, while capture location and ENSO weakly explained the composition of crustaceans and cephalopods. Skipjack and yellowfin tuna captured near coastal areas (Longitude<170°W) showed a greater diversity of prey compared to fish captured in oceanic regions of the Pacific, while Thunnus albacares showed a much more diverse stomach content than K. pelamis (21 fish, eight cephalopods and six crustaceans). Fish captured during La Niña events showed higher prey diversity compared to fish captured during El Niño. Tuna species best explained differences in gut microbiome to the Phylum level, while no model explained gut microbiome differences to the Order or Family level. This preliminary study shows that capture location and ENSO events explained differences in stomach content of K. pelamis and T. albacares, while tuna species best explained gut microbiome assemblages to the Phylum level.

Hemispheric Specialization of the Primate Inferior Parietal Lobule - Sam Vickery; Simon B Eickhoff; Patrick Friedrich (Neuroscience Bulletin, 2022)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Variability of Skin Pharmacokinetic Data: Insights from a Topical Bioequivalence Study Using Dermal Open Flow Microperfusion - Manfred Bodenlenz; Thomas Augustin; Thomas Birngruber; Katrin I. Tiffner; Beate Boulgaropoulos; Simon Schwingenschuh; Sam G. Raney; Elena Rantou; Frank Sinner (Pharmaceutical Research, 2020)
Purpose Dermal open flow microperfusion (dOFM) has previously demonstrated its utility to assess the bioequivalence (BE) of topical drug products in a clinical study. We aimed to characterize the sources of variability in the dermal pharmacokinetic data from that study. Methods Exploratory statistical analyses were performed with multivariate data from a clinical dOFM-study in 20 healthy adults evaluating the BE, or lack thereof, of Austrian test (T) and U.S. reference (R) acyclovir cream, 5% products. Results The overall variability of logAUC values (CV: 39% for R and 45% for T) was dominated by inter-subject variability (R: 82%, T: 91%) which correlated best with the subject’s skin conductance. Intra-subject variability was 18% (R) and 9% (T) of the overall variability; skin treatment sites or methodological factors did not significantly contribute to that variability. Conclusions Inter-subject variability was the major component of overall variability for acyclovir, and treatment site location did not significantly influence intra-subject variability. These results support a dOFM BE study design with T and R products assessed simultaneously on the same subject, where T and R treatment sites do not necessarily need to be next to each other. Localized variation in skin microstructure may be primarily responsible for intra-subject variability.

Integration of Transverse Isotropy in the Instantaneous Behaviour of Geomaterials with Application to Numerical Modelling of Underground Structures - Inès Djouadi; Richard Giot; Simon Raude; Sam Cuvilliez; François Laigle; Roméo Fernandes (Geotechnical and Geological Engineering, 2020)

Rage Against the Machine: Advancing the study of aggression ethology via machine learning. - Nastacia L. Goodwin; Simon R.O. Nilsson; Sam A. Golden (Psychopharmacology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Measuring climate resilience by linking shocks to development outcomes - Sam Barrett; Nick Brooks; Novi Quadrianto; Simon Anderson; Bayu Nebsu (Climate and Development, 2020)

Compound Specific Trends of Chemical Defences in Ficus Along an Elevational Gradient Reflect a Complex Selective Landscape - Martin Volf; Juuso E. Laitila; Jorma Kim; Legi Sam; Katerina Sam; Brus Isua; Mentap Sisol; Carl W. Wardhaugh; Frantisek Vejmelka; Scott E. Miller; George D. Weiblen; Juha-Pekka Salminen; et al. (Journal of Chemical Ecology, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Cardiovascular Effects of Indoor Air Pollution from Solid Fuel: Relevance to Sub-Saharan Africa - Ana Olga Mocumbi; Simon Stewart; Sam Patel; Wael K. Al-Delaimy (Current Environmental Health Reports, 2019)

Drier tropical forests are susceptible to functional changes in response to a long‐term drought - Jesús Aguirre‐Gutiérrez; Imma Oliveras; Sami Rifai; Sophie Fauset; Stephen Adu‐Bredu; Kofi Affum‐Baffoe; Timothy R. Baker; Ted R. Feldpausch; Agne Gvozdevaite; Wannes Hubau; Nathan J. B. Kraft; Simon L. Lewis; et al. (Ecology Letters, 2019)
Climatic changes have profound effects on the distribution of biodiversity, but untangling the links between climatic change and ecosystem functioning is challenging, particularly in high diversity systems such as tropical forests. Tropical forests may also show different responses to a changing climate, with baseline climatic conditions potentially inducing differences in the strength and timing of responses to droughts. Trait‐based approaches provide an opportunity to link functional composition, ecosystem function and environmental changes. We demonstrate the power of such approaches by presenting a novel analysis of long‐term responses of different tropical forest to climatic changes along a rainfall gradient. We explore how key ecosystem's biogeochemical properties have shifted over time as a consequence of multi‐decadal drying. Notably, we find that drier tropical forests have increased their deciduous species abundance and generally changed more functionally than forests growing in wetter conditions, suggesting an enhanced ability to adapt ecologically to a drying environment.

Development of an In Vitro PIV Setup for Preliminary Investigation of the Effects of Aortic Compliance on Flow Patterns and Hemodynamics - Martin Büsen; Christian Arenz; Michael Neidlin; Sam Liao; Thomas Schmitz-Rode; Ulrich Steinseifer; Simon J. Sonntag (Cardiovascular Engineering and Technology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

The evolution of genomic islands by increased establishment probability of linked alleles - Sam Yeaman; Simon Aeschbacher; Reinhard Bürger (Molecular Ecology, 2016)
Genomic islands are clusters of loci with elevated divergence that are commonly found in population genomic studies of local adaptation and speciation. One explanation for their evolution is that linkage between selected alleles confers a benefit, which increases the establishment probability of new mutations that are linked to existing locally adapted polymorphisms. Previous theory suggested there is only limited potential for the evolution of islands via this mechanism, but involved some simplifying assumptions that may limit the accuracy of this inference. Here, we extend previous analytical approaches to study the effect of linkage on the establishment probability of new mutations and identify parameter regimes that are most likely to lead to evolution of islands via this mechanism. We show how the interplay between migration and selection affects the establishment probability of linked vs. unlinked alleles, the expected maximum size of genomic islands, and the expected time required for their evolution. Our results agree with previous studies, suggesting that this mechanism alone is unlikely to be a general explanation for the evolution of genomic islands. However, this mechanism could occur more readily if there were other pre‐adaptations to reduce local rates of recombination or increase the local density of mutational targets within the region of the island. We also show that island formation via erosion following secondary contact is much more rapid than island formation from de novo mutations, suggesting that this mechanism may be more likely.

Evidence‐based conservation: reply to Tepedino et al. - Gretchen Lebuhn; Sam Droege; Edward F. Connor; Barbara Gemmill‐Herren; Simon G. Potts; Robert L. Minckley; Robert P. Jean; Emanuel Kula; David W. Roubik; Karen W. Wright; Gordon Frankie; Frank Parker (Conservation Biology, 2015)

A fire‐driven shift from forest to non‐forest: evidence for alternative stable states? - Michael-Shawn Fletcher; Sam W. Wood; Simon G. Haberle (Ecology, 2014)
We test the validity of applying the alternative stable state paradigm to account for the landscape‐scale forest/non‐forest mosaic that prevails in temperate Tasmania, Australia. This test is based on fine‐scale pollen, spore, and charcoal analyses of sediments located within a small patch of non‐forest vegetation surrounded by temperate forest. Following nearly 500 years of forest dominance at the site, a catastrophic fire drove an irreversible shift from a forested Cyperaceae– Sphagnum wetland to a non‐forested Restionaceae wetland at ca. 7000 calibrated (cal) yr BP. Persistence of the non‐forest/Restionaceae vegetation state over 7000 years, despite long fire‐free intervals, implies that fire was not essential for the maintenance of the non‐forest state. We propose that reduced interception and transpiration of the non‐forest state resulted in local waterlogging, presenting an eco‐hydrological barrier to forest reestablishment over the succeeding 7000 years. We further contend that the rhizomatous nature of the non‐forest species presented a reinforcing eco‐physical barrier to forest development. Our results satisfy a number of criteria for consideration as an example of a switch between alternative stable states, including different origin and maintenance pathways, and they provide insights into the role of threshold dynamics and hysteresis in forest–non‐forest transitions.

Detecting Insect Pollinator Declines on Regional and Global Scales - Gretchen Lebuhn; Sam Droege; Edward F. Connor; Barbara Gemmill‐Herren; Simon G. Potts; Robert L. Minckley; Terry Griswold; Robert Jean; Emanuel Kula; David W. Roubik; Jim Cane; Karen W. Wright; et al. (Conservation Biology, 2013)
Recently there has been considerable concern about declines in bee communities in agricultural and natural habitats. The value of pollination to agriculture, provided primarily by bees, is >$200 billion/year worldwide, and in natural ecosystems it is thought to be even greater. However, no monitoring program exists to accurately detect declines in abundance of insect pollinators; thus, it is difficult to quantify the status of bee communities or estimate the extent of declines. We used data from 11 multiyear studies of bee communities to devise a program to monitor pollinators at regional, national, or international scales. In these studies, 7 different methods for sampling bees were used and bees were sampled on 3 different continents. We estimated that a monitoring program with 200–250 sampling locations each sampled twice over 5 years would provide sufficient power to detect small (2–5%) annual declines in the number of species and in total abundance and would cost U.S.$2,000,000. To detect declines as small as 1% annually over the same period would require >300 sampling locations. Given the role of pollinators in food security and ecosystem function, we recommend establishment of integrated regional and international monitoring programs to detect changes in pollinator communities. Detección de Declinaciones de Insectos Polinizadores a Escalas Regional y Global

Movements of adult female Weddell seals during the winter months - Sam Lake; Harry Burton; Simon Wotherspoon (Polar Biology, 2006)

Impairment of specific episodic memory processes by sub-psychotic doses of ketamine: the effects of levels of processing at encoding and of the subsequent retrieval task - Garry D. Honey; Rebekah A. E. Honey; Sam R. Sharar; Danielle C. Turner; Edith Pomarol-Clotet; Dharshan Kumaran; Jon S. Simons; Xiangen Hu; Michael D. Rugg; Edward T. Bullmore; Paul C. Fletcher (Psychopharmacology, 2005)

Fever and phenotype: transgenerational effect of disease on desert locust phase state - Sam L. Elliot; Simon Blanford; Charlotte M. Horton; Matthew B. Thomas (Ecology Letters, 2003)
Natural enemy attack can cause transgenerational shifts in phenotype such that offspring are less vulnerable to future attack. Desert locusts ( Schistocerca gregaria ) show density‐dependent variation in their resistance to pathogens, such that they are less vulnerable to pathogens when in the high‐density gregarious phase state (when they would probably be more exposed to pathogens) than when in the solitarious phase state. We therefore hypothesized that infected gregarious parents would maintain this phenotype in their offspring. We infected gregarious desert locust nymphs with the fungal pathogen Metarhizium anisopliae var. acridum , and allowed them to survive to reproduction by means of behavioural fever. The phase state of the locust offspring was assessed by their colouration and behavioural assays. Contrary to our hypothesis, we found an increase in solitarization in the infected population (14.6% solitarious offspring from infected parents, vs.